Pharmacokinetics of immediate and sustained-release formulations of paroxetine: Population pharmacokinetic approach to guide paroxetine personalized therapy in chinese psychotic patients - Li, Xiao-lin; Huang, Shan-qing; Xiao, Tao; Wang, Xi-pei; Kong, Wan; Liu, Shu-jing; Zhang, Zi; Yang, Ye; Huang, Shan-shan; Ni, Xiao-jia; Lu, Hao-yang; Zhang, Ming; et al. (Frontiers in Pharmacology, 2022)
Paroxetine is one of the most potent selective serotonin reuptake inhibitors (SSRI) approved for the treatment of depression, panic disorder, and obsessive-compulsive disorder. Paroxetine’s pharmacokinetic (PK) variability is known to be related to nonlinear metabolism and genetic polymorphisms. The present study aimed to develop a population PK (PPK) model for paroxetine in Chinese patients, which was used to define the PK parameters of paroxetine and quantify the effect of clinical and baseline demographic factors on these PK characteristics. The study included 184 inpatients with psychosis (103 females and 81 males), with a total of 372 serum concentrations of paroxetine for PPK analyses. The total dosage regimens ranged from 20 to 75mg. A one-compartment model with first-order absorption was used to describe the PKs of paroxetine. Covariate analysis revealed that dose, formulation, and sex had a significant effect on the PK parameters of paroxetine; however, no obvious genetic effect of CYP2D6 enzymes was found relative to the concentrations of paroxetine in Chinese patients. The population estimates of the apparent volume of distribution (V/F) and apparent clearance (CL/F) were 8850 L and 21.2 L/h, respectively. The CL/F decreased 1-2-fold for each 10 mg dose increase, whereas the different formulations caused a decrease in V/F of 66.6%. Sex was found to affect bioavailability (F), which decreased F by 47.5%. Females had higher F values than males. This PPK model described data from patients with psychosis who received paroxetine immediate-release tablets (IR-T) and/or sustained-release tablets (SR-T). Paroxetine trough concentrations and relative bioavailability were different between formulations and sex. The altered serum concentrations of paroxetine resulting from individual variants and additive effects need to be considered, to optimize the dosage regimen for individual patients.